Geology and Petrography of Subong, Gua Musang, Kelantan - Law, Mer Rei (2016)
The study is focused on the geology and petrography of rocks in Subong, Gua Musang, Kelantan. Subong is located at the South of Gua Musang and geologically covered by the Gua Musang Formation which aged Middle Permian to Middle Triassic, by Yin (1963). The stratigraghy and rock tmits of Subong were studied and found out to compose of argillaceous facies, arenaceous facies, calcareous facies, granitic facies and metamorphic facies. These microscopic rock units were identiﬁed and classiﬁed as Gua Musang Formation. The petrographical analysis was made to examine the mineralogy and texture and supported that these rock units are lie within the Gua Musang Fonnation. The provenance of the sandstone and siltstone showed that the source rock of sedimentary rocks in study area was recycled orogeny. Besides petrography and provenance, it was also found that the chemical weathering intensity of the study area is low due to the high contents of feldspar than the stable mineral quartz.